2018
DOI: 10.1177/1078390318761790
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing–Based Compliance/Adherence Therapy Interventions to Improve Psychiatric Symptoms of People With Severe Mental Illness: Meta-Analysis

Abstract: These findings support the effectiveness of MI-based CAT interventions. Session length and dose effect should be considered when tailoring MI to clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Psychotropic medications are established first-line treatment for controlling psychiatric symptoms (Stern et al, 2018); however, nonadherence to prescriptions is common among people with SMI and the leading cause of relapse in mental illness (Barkhof et al, 2012). Systematic and meta-analytic research evidence supports the use of psychoeducation (Zhao et al, 2015), motivational interviewing (Wong-Anuchit et al, 2018), and behavioral strategies (Kreyenbuhl et al, 2016) to improve medication adherence for people with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic medications are established first-line treatment for controlling psychiatric symptoms (Stern et al, 2018); however, nonadherence to prescriptions is common among people with SMI and the leading cause of relapse in mental illness (Barkhof et al, 2012). Systematic and meta-analytic research evidence supports the use of psychoeducation (Zhao et al, 2015), motivational interviewing (Wong-Anuchit et al, 2018), and behavioral strategies (Kreyenbuhl et al, 2016) to improve medication adherence for people with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…While this intervention showed some early promise for improving insight, adherence, attitudes towards medication and rehospitalisation rates in an inpatient sample (Kemp et al, 1996(Kemp et al, , 1998, further studies failed to replicate these positive findings for improving adherence (Barkhof et al, 2013;Byerly et al, 2005;O'Donnell et al, 2003), and a well-conducted, adequately powered RCT found adherence therapy to be ineffective in improving adherence, psychotic symptoms or quality of life in people with schizophrenia (Gray et al, 2006). Some evidence for efficacy has been provided by subsequent studies (Chien et al, 2019;Gray et al, 2016;Wong-Anuchit et al, 2019), although this generally relates to improving psychiatric symptoms rather than adherence directly.…”
Section: Interventions To Improve Adherencementioning
confidence: 99%
“…When used by clinicians in a therapeutic interaction, MI is not the lone intervention and is often combined with other forms of therapeutic services to promote healthy behaviours (Wong‐Anuchit et al . 2018). Motivational interviewing could therefore be used to focus on exercise engagement and support consumers to increase motivation and behaviour change towards introducing exercise (Madson et al .…”
Section: Discussionmentioning
confidence: 99%